2012
DOI: 10.1007/s10695-011-9599-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic low pH exposure affects the seawater readiness of juvenile Pacific sockeye salmon

Abstract: Chronic exposure to water of low pH during the freshwater life stage of Pacific salmonids is presently the cause for concern due to its potential to reduce subsequent performance in the marine environment. Sockeye fry (0+) were raised under sublethal long-term, low pH conditions (pH 4.8-6.8) in soft water and assessed for effects on freshwater growth, stress physiology, and seawater tolerance following smoltification. Fish gained significantly lower mass (average 46% of control [pH 6.8] values) and had lower c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…The acclimation capacity to low‐pH environments seems to be species‐specific, where some species exhibit increased growth and no ionoregulatory disturbance, such as rainbow trout (Dockray, Morgan, Reid & Wood, ; Dockray et al., ), while others are extremely sensitive and cannot acclimate, such as juvenile Pacific sockeye salmon ( Oncorhynchus nerka ) (Kennedy & Picard, ). Low‐pH environment has been associated with high mortality (Abbink et al., ), reduced feed intake and growth (Kennedy & Picard, ), increased ion permeability of the gill integumental epithelium (McDonald et al., ; Wendelaar Bonga, ), significant misbalances of sodium and chloride ions (Butler, Day & Namba, ) and disturbances in haematology, fluid volume distribution and circulatory function (Milligan & Wood, ). The majority of these studies addressed the effect of low pH in the context of acidification of freshwater ecosystems, where other variables resulting from a low‐pH environment, such as ammonium (NH 4 ‐N) (Eshchar et al., ) and aluminium (Brown et al., ; Fivelstad et al., ) toxicity likely affected fish performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The acclimation capacity to low‐pH environments seems to be species‐specific, where some species exhibit increased growth and no ionoregulatory disturbance, such as rainbow trout (Dockray, Morgan, Reid & Wood, ; Dockray et al., ), while others are extremely sensitive and cannot acclimate, such as juvenile Pacific sockeye salmon ( Oncorhynchus nerka ) (Kennedy & Picard, ). Low‐pH environment has been associated with high mortality (Abbink et al., ), reduced feed intake and growth (Kennedy & Picard, ), increased ion permeability of the gill integumental epithelium (McDonald et al., ; Wendelaar Bonga, ), significant misbalances of sodium and chloride ions (Butler, Day & Namba, ) and disturbances in haematology, fluid volume distribution and circulatory function (Milligan & Wood, ). The majority of these studies addressed the effect of low pH in the context of acidification of freshwater ecosystems, where other variables resulting from a low‐pH environment, such as ammonium (NH 4 ‐N) (Eshchar et al., ) and aluminium (Brown et al., ; Fivelstad et al., ) toxicity likely affected fish performance.…”
Section: Discussionmentioning
confidence: 99%
“…Low pH conditions have also been used in RAS producing other fish species, such as Dover sole ( Solea solea ), African Catfish ( Clarias gariepinus ) and Nile tilapia ( Oreochromis niloticus) (Mota et al., ). However, several adverse effects have been reported for fish exposed to low environmental pH, such as reduced growth and feed intake (Abbink et al., ; Kennedy & Picard, ). Moreover, low pH can increase cortisol level, which causes a transient depression on the nonspecific immune activity (Brown, MacLatchy, Hara & Eales, ) and can result in plasma acidosis and a concomitant reduction in plasma ions (McDonald, Walker, Wilkes & Wood, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While fish can habituate to some chronic stressors, sustained plasma cortisol levels similar to those used in this study have been observed in response to diverse stressors of anthropogenic and natural origins. For example, chronic exposure to aluminum, copper, selenium or low environmental pH can result in prolonged elevations in plasma cortisol levels (Craig et al 2009, Wiseman et al 2011, Kennedy & Picard 2012, Grassie et al 2013. In salmonids, sustained increases in cortisol levels are also associated with social subordination (Gilmour et al 2005) and with specific phases of the life cycle such as smolting (Nilsen et al 2008) and sexual maturation (Fuzzen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The pH is an essential parameter in ecological environments and biological organisms, and different pH values can influence the growth rate of cells, metabolic rates, cell division, and differentiation [1][2][3][4]. Some researchers have shown that the carbon cycles of marine coral ecosystems and even of global ecosystems are affected by fluctuating pH values, and pH fluctuations caused by wastewater discharge into upstream rivers will also affect downstream ecosystems [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%